Prognostic Value of Vascular-Expressed PSMA and CD248 in Urothelial Carcinoma of the Bladder - Li, Yu; Zhang, Keying; Yang, Fa; Jiao, Dian; Li, Mingyang; Zhao, Xiaolong; Xu, Chao; Liu, Shaojie; Li, Hongji; Shi, Shengjia; Yang, Bo; Yang, Lijun; et al. (Frontiers in Oncology, 2021)
Background: Urothelial Carcinoma of the Bladder (UCB) is a common cancer of the urinary system. Despite substantial improvements in available treatment options, the survival outcome of patients with advanced UCB is unsatisfactory. Therefore, it is necessary to identify new prognostic biomarkers for monitoring and therapy guidance of UCB. In recent years, prostate-specific membrane antigen (PSMA) and CD248 have been identified promising candidate biomarkers. Methods: In this study, we first examined PSMA and CD248 expression in tissues from 124 patients with UCB using immunohistochemical and immunofluorescent staining. We then analyzed the association between expression of the two biomarkers and other clinicopathological features and prognosis. Finally, we performed bioinformatic analysis of CD248 and FOLH 1 (PSMA) using the TCGA-BLCA dataset to explore the underlying mechanism of PSMA and CD248 in the progression of UCB. Results: Among the 124 cases, PSMA and CD248 were confirmed to be expressed in tumor-associated vessels. Vascular PSMA and CD248 expression levels were associated significantly with several deteriorated clinicopathological features. Furthermore, using univariate and multivariate Cox analyses, high vascular PSMA and CD248 expression levels were observed to be associated significantly with poor prognosis in patients with UCB. As risk factors, both PSMA and CD248 expression showed good performance to predict prognosis. Furthermore, combining these vascular molecules with other clinical risk factors generated a risk score that could promote predictive performance. Bioinformatic analysis showed that both PSMA and CD248 might contribute to angiogenesis and promote further progression of UCB. Conclusion: Both PSMA and CD248 are specifically expressed in the tumor-associated vasculature of UCB. These two molecules might be used as novel prognostic biomarkers and vascular therapeutic targets for UCB.